Selected somatic marks and their formation in workers of the machine industry - Tuszyński, Krzysztof; Woźniak, Witold (Anthropological Review, 1976)
The authors examined 4 professional groups (turners, grinders, milling machine workers and clerks) engaged in the machine industry works. In all. 388 men were tested. 16 biological marks were investigated which unabled to work out a somatic characteristic. The picture dereived from the younger workers (training period 5 - 15 years) is presented apart from that of the older workers group with a working period 15-25 years. A likeness of the somatic build of the manual workers was found in the various groups distinct from that of the office workers group. Within the same professional group there was some likeness of marks; this can be related with the character of their work. Differences were noted between the younger and older workers. The authors suggest that when designing technical plant in the machine industry, the morphological differentiation of the workers should be taken into account.